ANÁLISIS DE LOS MOVIMIENTOS INDÍGENAS DE LA PROVINCIA DE CHIMBORAZO EN LA PRESIDENCIA DE RAFAEL CORREA E IMPLEMENTACIÓN DE POLÍTICAS PÚBLICAS - Centeno Moyón, Verónica Janneth (2020)
This investigation starts from the conflict established between the former President of the Republic Rafael Correa and the Ecuadorian indigenous movement, which arose around the praxis of pluractionality, causing confrontations, such events caused the ex-president to strengthen the participation of grassroots organizations. Reason why this study analyzes the relationship of the Chimborazo indigenous movement and the impact of public policies implemented in the indigenous sectors of the province, during the term of the economist Rafael Correa To arrive at this analysis, the non-experimental qualitative research design was used, as well as the hemerographic technique applied in the Municipal Library of Riobamba, with the gathering of information regarding the position of the Ecuadorian indigenous movement prior to the presidential elections from 2006. The interview with its respective instrument, the question guide, made it possible to collect criteria from the current vice-president of COMICH Carmen Tiupúl and pastor Jorge Muyolema, former member of CONPOCIIECH and current leader of FEINE, regarding the relationship of the organizations with ex-president Rafael Correa. In the next stage of the investigation that contemplates the impact of the public policies implemented in the indigenous sector of Chimborazo, bibliographic information was reviewed as well as criteria of the leaders of the mentioned organizations. The set of these techniques with their respective instruments, allowed the analysis of pertinent information and to fulfill the objectives established within the investigation.